Histopathological based retrospective study of oral keratotic white lesions in Manipal health systems-hospital - Gurung, P; Sherchan, JB; Pai, K (Scientific World, 2012)
Oral keratotic white lesions are a common problem that is encountered on routine clinical examination. Clinical appearance of the lesion may belie the true nature of the lesion. So a biopsy followed by histopathological diagnosis is the gold standard in evaluating these lesions for malignant potential or dysplasias. Objective: The aim of the present study is to evaluate the clinicopathologic findings of oral keratotic lesions. Materials and Methods: Oral biopsies of 61 cases of oral keratotic white lesions during the period from January 2006 to July 2009 were studied retrospectively at the Department of Pathology, Kasturba Medical College, Manipal by microscopy. Clinical details and records were obtained from the medical records department. Results: In 61 cases of oral keratotic white lesions the age distribution ranged from 29 to 86 years. 66% were males while 34% were females and most lesions occurred between 31 and 70 years. The buccal mucosa was the most common site of lesion in 35% patients. Only 15 cases had some personal habits and 8/15 cases (53%) showed dysplasia. 12/ 54 cases (22%) of homogenous leukoplakia displayed dysplasia, of which 11 cases (92%) showed mild dysplasia and 1 case (8%) showed moderate dysplasia. Of the 4 cases of speckled leukoplakia, 75% showed dysplasia- mild, moderate and severe. 2/3 cases (66%) of verrucous leukoplakia displayed dysplasia- moderate and severe. There were 41 cases consistent with leukoplakia (67%), of which 22% showed epithelial hyperplasia and hyperkeratosis, 12 cases showed mild dysplasia, 3 cases moderate dysplasia and 2 cases showed severe dysplasia. Benign keratosis formed the largest group (35%) among the 61 cases. Of the 61 cases 17 (27%) showed dysplasia of which 19% was mild dysplasia, 5% was moderate dysplasia and 3% was severe dysplasia. Most frequent histomorphological feature seen in this study was nuclear pleomorphism in 21/ 27 cases (78%). There were 12 cases (71%) of dysplasia in males and 5 cases (28%) of dysplasia in females. There was 1 case of Progressive verrucous leukoplakia in an 86 year old female patient. There were 3 cases (5%) each of oral lichen planus, lichenoid dysplasia and lichenoid keratosis in the present study. 6 cases (9%) of candidiasis was seen among the 61 biopsies. In the study there was 1 case (2%) each of verrucous carcinoma, squamous cell carcinoma and micro-invasive squamous cell carcinoma. Conclusions: Oral keratotic white lesions demonstrate a wide spectrum of histopathological features from benign lesions to dysplastic lesions to carcinoma in situ to invasive ones. Scientific World, Vol. 10, No. 10, July 2012 p70-76 DOI: http://dx.doi.org/10.3126/sw.v10i10.6866